Social Construction of Technology in VR Adoption for Science Education - Muslich, Adipurwa (UI Scholars Hub, 2025)
VR has emerged as a promising tool for revolutionizing science education, offering immersive and interactive experiences that can enhance student understanding. It holds significant potential as a communication medium for explaining the complexities of science in classroom settings. Despite its potential, VR’s penetration in science education remains limited. This research explored the facets influencing VR adoption in education, focusing on science teachers' perspectives in Jakarta. Using a qualitative approach, the study investigates how the SCOT concept, grounded in communication theory, affects the adoption of VR in the educational sector. Key themes identified included the role of networking, school culture, socioeconomic disparities, policies, and pedagogical considerations. Teacher characteristics—such as openness to innovation and collaborative skills—were found to act as catalysts for adoption. Conversely, resistance to change and limited access to resources emerged as significant obstacles. The research underscores communication plays a pivotal role in the diffusion of VR technology in educational contexts. The findings offer valuable insights for policymakers, educators, and technology developers. This research contributes to education sector by providing a nuanced understanding about social construction in VR adoption, complementing prior quantitative studies.